The dark side of the Internet: protecting yourself and your family from online criminals - Bocij, Paul (Praeger, 2006)
Cyberterror and information warfare -- Cyberterror -- A digital Pearl Harbor? -- Information warfare -- Terrorist uses of technology -- Further information -- Cyberattacks -- Assessing the threat -- Safety and prevention -- Further information -- Malicious software -- Viruses, trojans, and worms -- Types of computer viruses -- How many viruses are there? -- The damage caused by viruses -- How viruses spread -- Who writes viruses? -- Why people write viruses -- Detecting viruses -- Dealing with viruses -- Choosing antivirus software -- Safety and prevention -- Virus hoaxes -- More about trojans -- Dealing with trojans -- Safety and prevention -- Further information -- Spyware and adware -- What is spyware? -- Adware -- Why create spyware? -- The extent of the problem -- Contracting spyware -- Dealing with spyware and adware -- Safety and prevention -- Further information -- Identity theft and fraud -- Identity theft -- What is identity theft? -- Identity theft and the internet -- The extent of the problem -- Identifying phishing e-mails -- Safety and prevention -- Further information -- E-mail fraud -- Advance fee frauds -- Foreign lotteries -- Nigerian 419 fraud -- Other e-mail frauds -- Safety and prevention -- Further information -- Auctions and other forms of fraud -- Auction fraud -- Safety and prevention -- Other online frauds -- Safety and prevention -- Further information -- Junk e-mail -- What is spam? -- The extent of the problem -- The cost of spam -- Why spam exists? -- Dealing with spam -- Safety and prevention -- Resources for dealing with spam -- Further information -- Intellectual property theft -- Software piracy -- Safety and prevention -- Music and movie piracy -- Further information -- Online relationships and deviance -- Cyberstalking -- What is cyberstalking? -- The extent of the problem -- Who are the cyberstalkers? -- Who is most at risk? -- New and emerging forms of cyberstalking -- Safety and prevention -- Further information -- Online relationships -- Social isolation -- White knights -- Hero syndrome -- Further information -- Deviant subcultures -- Cults and hate speech -- Deviant subcultures and addiction -- Safety and prevention -- Further information